Poor development. An epistemic rethinking to the field of social justice - Jiménez, Manuel Antonio (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2020)
Development studies is concerned with two issues: the development of normative theories of development and justice (development discourse), and the empirical study of the effects of interventions and their impact on the global policy context (development policy). These distinct theoretical aims of the discipline lead to epistemological difficulties in practice. In this paper I argue that development studies suffer from two main conceptual deficiencies. The first one corresponds to an analytical incapability for providing a definitive version of social justice that is simultaneously impartial and plural. The second weakness involves an empirical deficiency related to development discourse and current policies and practices. Identifying both epistemic deficiencies inherently embedded into what development has traditionally been about, may help to shed light on its analytical and technical boundaries and thus its ability to truly carry out its stated goals. To that end, this paper focuses on highlighting the consequences of these two epistemic oversights. I conclude that the field of development has no other alternative than (re)turning to its epistemic roots to adequately review the very essence of its conceptualization and effects.